Adnominal possessive constructions in Mordvin, Mari and Permic - Pleshak, Polina (Eesti ja soome-ugri keeleteaduse ajakiri. Journal of Estonian and Finno-Ugric Linguistics, 2018)
This paper deals with adnominal possessive constructions in Moksha, Erzya, Meadow Mari, Hill Mari, Izhma Komi and Udmurt. The two main constructions that encode possessive relations in all the languages of the sample are the same: Dependentmarking and Double-marking. Izhma Komi also uses Head-marking and Juxtaposition. However, a more fine-grained analysis helps to find out many differences between the languages of the sample. Firstly, restrictions on the use of the genitive case and possessive markers can be slightly different in these languages. Secondly, there are factors that influence marking of NP elements (both the Head and the Dependent) in different ways. These factors are semantic relations, animacy hierarchy and syntactic function of an NP.Аннотация. Полина Плешак: Посессивные конструкции в мордовских, марийских и пермских языках. В данной статье обсуждаются результаты исследования приименных посессивных конструкций в мокшанском, эрзянском, луговом марийском, горномарийском, ижемском коми и удмуртском. Две основные стратегии, кодирующие посессивные отношения во всех рассматриваемых языках, – зависимостное маркирование и двойное маркирование, а также дополнительно вершинное маркирование и конструкция с соположением в ижемском коми. Однако более детальный анализ позволяет выявить большое количество различий между языками выборки. Во-первых, как генитив, так и посессивные показатели имеют разные области применения в разных языках. Во-вторых, существуют факторы, по-разному влияющие на маркирование членов ИГ (как вершины, так и зависимого). Таковыми являются семантические отношения, иерархия одушевлённости и синтаксическая позиция ИГ.Ключевые слова: внутригенетическая типология, посессивные конструкции, зависимостное маркирование, двойное маркирование, генитив, посессивный показатель, семантические отношения, иерархия одушевлённости, финно-угорские языкиKokkuvõte. Polina Pleshak: Adnominaalsed possessiivkonstruktsioonid mordva, mari ja permi keeltes. Artikkel käsitleb adnominaalseid ...